The Analysis of Sustainability Report Disclosure in the Companies listed on the IDX Year 2014 – 2016 - Arumsari, Yogi; Asrori, Asrori (Universitas Negeri Semarang, 2019)
This research aims to get empirical evidence about the effect of firm size, leverage, audit committee, and environmental performance on sustainability report disclosure. The population of this research was all entities listed in the Indonesia Stock Exchange (IDX) during the years of 2014 – 2015 as many as 568 companies. In addition, sample was selected by using purposive sampling method. There were 22 companies as the final sample. During 2014 – 2015, there were 66 unit of analysis. Furthermore, hypotheses were examined by multiple regression analysis using SPSS 22.0 program. The results indicate that firm size and leverage have a negative and significant effect on sustainability report disclosure. Then, audit committee does not have a positive and significant effect on sustainability report disclosure and environmental performance has a positive and significant effect on sustainability report disclosure. Therefore, it can be concluded that environment performance can provide an important role in sustainability report disclosure.